Generic Self-Reported Questionnaires Measuring Self-Management: A Scoping Review. (July 2021) - Hudon, Émilie; Hudon, Catherine; Lambert, Mireille; Bisson, Mathieu; Chouinard, Maud-Christine
This study aimed to (1) identify generic questionnaires that measure self-management in people with chronic conditions, (2) describe their characteristics, (3) describe their development and theoretical foundations, and (4) identify categories of self-management strategies they assessed. This scoping review was based on the methodological framework developed by Arksey and O'Malley and completed by Levac et al. A thematic analysis was used to examine self-management strategies assessed by the questionnaires published between 1976 and 2019. A total of 21 articles on 10 generic, self-reported questionnaires were identified. The questionnaires were developed using various theoretical foundations. The Patient Assessment of Self-Management Tasks and Partners in Health scale questionnaires possessed characteristics that made them suitable for use in clinical and research settings and for evaluating all categories of self-management strategies. This study provides clinicians and researchers with an overview of generic, self-reported questionnaires and highlights some of their practical characteristics.